2004
DOI: 10.1023/b:neon.0000041885.09226.2d
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategies for Treating Patients with Pineal Region Tumors

Abstract: Optimal management of pineal region tumors depends on securing an accurate histologic diagnosis to facilitate management customized to the nuances of specific pathologies. As an initial step, surgical intervention by either stereotactic biopsy or open surgery is necessary to obtain tissue for pathologic examination. Stereotactic biopsy has the benefit of relative ease and minimal morbidity but is associated with greater likelihood of diagnostic inaccuracy compared to open surgery where more extensive tissue sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 78 publications
1
69
0
4
Order By: Relevance
“…In the case of the intraoperative diagnosis of germinomas during instantaneous section, further resection is unnecessary due to its high sensitivity to radiation and/or chemotherapy (7,8). If a malignant germ-cell tumor is strongly suspected preoperatively, due to elevated concentrations of α-fetoprotein (AFP) and/or β-human chorionic gonadotropin (β-4 HCG) measured by preoperative examination of serum or cerebrospinal fluid (CSF) (1,9), chemotherapy combined with radiation therapy may precede the surgery, and neurosurgical resection should only be planned for residual tumors (7). If the patient's symptoms are caused by obstructive hydrocephalus, its treatment should precede the tumor resection.…”
Section: Neurosurgical Indication and Timing Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the intraoperative diagnosis of germinomas during instantaneous section, further resection is unnecessary due to its high sensitivity to radiation and/or chemotherapy (7,8). If a malignant germ-cell tumor is strongly suspected preoperatively, due to elevated concentrations of α-fetoprotein (AFP) and/or β-human chorionic gonadotropin (β-4 HCG) measured by preoperative examination of serum or cerebrospinal fluid (CSF) (1,9), chemotherapy combined with radiation therapy may precede the surgery, and neurosurgical resection should only be planned for residual tumors (7). If the patient's symptoms are caused by obstructive hydrocephalus, its treatment should precede the tumor resection.…”
Section: Neurosurgical Indication and Timing Of Surgerymentioning
confidence: 99%
“…If the patient's symptoms are caused by obstructive hydrocephalus, its treatment should precede the tumor resection. Temporary ventricular drainage, a permanent ventriculo-peritoneal (VP) shunt, or an endoscopic third ventriculostomy are possible treatments for obstructive hydrocephalus (9). Surgical resection of the tumor should then be performed.…”
Section: Neurosurgical Indication and Timing Of Surgerymentioning
confidence: 99%
“…Generally used for pediatric patients and for supratentorial approaches (Bruce et al, 1996). The head is neutrally fixed and slight flexed but the anatomical landmarks are inverted.…”
Section: Prone Positionmentioning
confidence: 99%
“…Under microscope magnification, severing the bridging veins between cerebellum and tentorium is a crucial point to gain the corridor carrying out the approach through. As some authors reported (Ueyama et al, 1998;Bruce & Stein, 1993;Fain et al, 1994;Page 1977), bridging veins in the midline can be sacrificed but this could lead to cerebellar venous infarction and consequent swelling. The arachnoidal adhesions should be released on the surface of cerebellum and all along the tentorial incisura as well, where they are particularly thickened.…”
Section: Infratentorial-supracerebellar Approachmentioning
confidence: 99%
“…The surgical major morbidity rate associated with pineocytomas is comprised between 3% and 6.8%, and permanent minor morbidity rate was 3-28%. The risk of surgical mortality associated with pineocytoma removal has been reduced in these last 20 years, but it remains less than 2% (Friedman et al, 2001, Bruce & Ogden, 2004. The role of adjuvant RT has not been clearly delineated.…”
Section: Pineocytomamentioning
confidence: 99%